China 2020 : the next decade for the People's Republic of China - Brown, Kerry, 1967- (Chandos Asian studies series., 2010)
"This book presents eight separate essays and provides the reader with a unique perspective and objective judgement of where China will stand by the end of the current decade. It is suitable reading for foreign policy practitioners, academics and anyone interested in one of the world's fastest-developing countries. The eight essays cover the following topics: China's internal politics; China's military; China's economy; China's international image and its international relations; China's legal development and; China's western regional development plans. China 2020 assesses where these issues stand today and highlights their likely trajectory over the following decade. A unique feature of this book is that it looks in particular at the policy impact, both for China and other countries, and the most and least likely outcomes for China's development in these areas. Readership: Policy makers dealing with China in government, and in companies with interests in or around China, and those who run non government organisations. Students and academics specialising in regional studies, and international studies and relations will also have an interest in this book."--Publisher's website